Selected Aspects of Today’s Leaders and Their Potential Development - David ULLRICH; Pavel SLÁDEK; Jan ZEZULA; Tereza TRNKOVÁ (Communications of International Proceedings, 2020)
The topic of leader and leadership is popular and frequently visited, and not just these days too. From the definitions and opinions on who actually a leader is, through various style and approaches to leadership all the way to competences or characteristics which should be found in a leader. Ability to improvise, development of professional intuition, creativity and openness to change are necessary attributes of a good leader. However, these require specific ways and methods which we discuss in this work. The point being the development and cultivation of both analytical and intuitive thinking, creative and critical approach, since both of these qualities are complementary to each other and their use alternates depending on the ongoing process. In this article we discuss selected aspects of thinking of people in general and leaders in particular, with the focus on cultivation and potential development of thinking which leads, through the leader, to achieving the goals of the group, company, or organization. Our goal was to introduce unconventional approaches to development of leaders’ way of thinking. These are not entirely usual but they allow for much deeper and vaster experiences, or open ways towards new, so far unexplored directions, which may be crucial for future leaders and may influence their future success.